Axial compressive behaviour of tapered CFDST stub columns with large void ratio. (April 2022) - Shi, Yan-Li; Ji, Sun-Hang; Wang, Wen-Da; Xian, Wei; Fan, Jia-Hao
Abstract: An experimental and numerical investigation on tapered concrete-filled double skin steel tubular (CFDST) stub columns with large void ratio under axial compression is presented in this paper. Twelve tapered CFDST specimens with different parameters, namely the void ratio and the diameter-to-thickness ratio of outer steel tube, are tested. The load versus deformation curves, failure modes, effects of different parameters are studied, respectively. It is found that tapered CFDST specimens with large void ratio experience the strength failure, and severely outward buckling occurs near the column top. The diameter-to-thickness ratio of outer steel tube and the void ratio engender a significant influence on the ultimate capacity and ductility of tapered CFDST columns. A finite element (FE) model is developed to predict test results, and to further analyze the working mechanism of tapered columns. The result shows that changing the tapered angle and void ratio has distinct effects on the position of failure section and distribution of peak load of tapered columns. A method considering the influence of failure section is finally proposed for calculating the ultimate capacity of tapered CFDST columns and a good predicted result is presented. Highlights: Twelve tapered CFDST stub columns with large void ratio are tested. Behaviour of tapered CFDST columns is analyzed by developed FE model. The influence of the void ratio and tapered angle on failure section is analyzed. Calculation formula for predicting the ultimate capacity is proposed.